Safety decision-making and planning mobile app for intimate partner violence prevention and response: randomised controlled trial in Kenya. Issue 7 (16th July 2020) - Decker, Michele R; Wood, Shannon N; Hameeduddin, Zaynab; Kennedy, S Rachel; Perrin, Nancy; Tallam, Catherine; Akumu, Irene; Wanjiru, Irene; Asira, Ben; Frankel, Ariel; Omondi, Benjamin; Case, James; et al.
Abstract : Introduction: Intimate partner violence (IPV) threatens women's health and safety globally, yet services remain underdeveloped and inaccessible. Technology-based resources exist, however, few have been adapted and tested in low-resource settings. We evaluate the efficacy of a community-partnered technology solution: culturally and linguistically adapted version of the myPlan app, a tailored safety decision-making and planning intervention, administrated by trained lay professionals. Methods: This randomised, controlled, participant-blinded superiority trial compares safety-related outcomes at baseline, immediate post intervention and 3-month follow-up among women at risk of and experiencing IPV in Nairobi, Kenya. Women were randomised (1:1 ratio) to: (1) myPlan Kenya (intervention); or (2) standard IPV referrals (control). Primary outcomes were safety preparedness, safety behaviour and IPV; secondary outcomes include resilience, mental health, service utilisation and self-blame. Results: Between April 2018 and October 2018, 352 participants (n=177 intervention, n=175 control) were enrolled and randomly assigned; 312 (88.6%, n=157 intervention, n=155 control) were retained at 3 months. Intervention participants demonstrated immediate postintervention improvement in safety preparedness relative to control participants (p=0.001). At 3 months, intervention participants reported increased helpfulness of safety strategies used relative to control participants (p=0.004); IPV reduced in both groups. Among women reporting the highest level of IPV severity, intervention participants had significant increase in resilience (p<0.01) compared with controls, and significantly decreased risk for lethal violence (p<0.01). Conclusions: Facilitated delivery of a technology-based safety intervention appropriately adapted to the context demonstrates promise in improving women's IPV-related health and safety in a low-resource, urban setting. Trial registration number: Pan African Clinical Trial Registry (PACTR201804003321122).